Factors which influence absenteeism among the operational non-exempt worker in Dufu Industries Sdn. Bhd, Penang, Malaysia - Husri, Hussain (2018)
Absenteeism at workplace has always been one of the most common problems in any industry. It is commonly understood as a worker or a group of workers remaining absent from work either continuously for a long period or repeatedly for short periods I due to many reasons. The present study has been designed a survey method to comprehend the causes for the worker absenteeism in the workplace. A total of 304 workers from operational sector were selected throughout purpose sample technique. From the study, 270 were returned and 257 were found to be usable. It was found out that, work place health problem, occupational stress and workload were significantly related to workers absenteeism in the company. Contrary to expectations, work environment was found not to be significant to absenteeism. To conclude, providing positive incentives to workers in the font of those motivational factors that normally influence workers to be absent is better than imposing the penalties for discouraging absenteeism. The best reward for the workers are influenced to a lesser extent by deterrent, loss of pay and benefits and loss of promotion opportunities. The company has to make rewards to their the workers or else providing counseling services to the workers by making them aware of these benefits would bring down the absenteeism in the workplace